P46 Dose-banding limits for commonly prescribed medications for children in the UK. Issue 9 (19th August 2020) - Rashed, Asia N; Tomlin, Stephen
Abstract : Aim: Currently, majority of prescribed medication doses are calculated according to a child's body weight without considering the available drug products for administration or the therapeutic range of the drug. This can lead to lack of consistency in dosing and drug administration errors, which affects many children of all ages treated with medicines. 1 There are no established standards for dose-banding in national or international healthcare systems. This project aimed to establish dose-banding limits for paediatric medicines, to be used for prescribing and administering accurate, safe, and effective drug doses. Method: A list of the most common oral prescribed medications was established from the medication dispensing database of four hospitals in the UK. Then the evidence for safe and effective dose ranges for each drug on the list was identified from paediatric reference books, Summary of Product Characteristics (SPC) and published literature. After using these data to develop dose bands based on body weight, we used a Delphi process to achieve healthcare professionals' consensus about the suggested dose bands for each drug on the list. Results: A total of 45 drugs for 45 specific indications were included. Four categories of dose-banding limits were established; drugs with 2-weight bands; 3-weight bands; 4-weight bands and 5-weight bands. Overall, for 53.3% (24/45) of the included drug, all their suggested dose-banding limits reached consensus after two rounds of Delphi. For 92% (22/24) of them, consensus was achieved on all their suggested bands in the first round. Only for 2 drugs the agreement was achieved after the second round. For the drugs included in 2-weight band and 5-weight band categories, all their suggested dose-banding limits received total consensus after round 1 of the Delphi process. For 9 drugs included in the 4-weight bands category, the agreement was achieved only on either one or two of their suggested dose bands. For 12 drugs, no agreement was reached on any of their suggested bands. Conclusion: The study results provide healthcare professionals with a set of recommended dose-banding limits for commonly prescribed drugs in the UK. These recommended limits could establish the basis for change in clinical practice to improve health care provided for children. Acknowledgement: This work is part of a larger project funded by the Neonatal and Paediatric Pharmacists Group. Reference: Rashed AN, Tomlin S, Arenas-Lópes S, et al . Evaluation of the practice of dose-rounding in paediatrics. Int J Pharm Pract 2019 May 29. doi:10.1111/ijpp.12549. [Epub ahead of print]